Mutation of Y(179) on phospholipase D2 (PLD2) upregulates DNA synthesis in a PI3K- and Akt-dependent manner - Di Fulvio, Mauricio (2007)
Phospholipase D2 (PLD2), one of the two mammalian members of the PLD family, has been implicated in cell proliferation, transformation, tumor progression and survival. However, as precise mechanistic details are still unknown, we investigated here if the PLD2 isoform would signal through the PI3K/AKT pathway. Transient expression of PLD2 in COS7 cells with either the WT or with a Y179F mutant, resulted in an increased basal phosphorylation of AKT in residues T(308) and S(473), in a PI3K-dependent manner. Transfection of PLD2-Y179F (but not the wild type) caused an increased (>2-fold) DNA synthesis even in the absence of extracellular stimuli. Other signaling mechanisms downstream such PLD/PI3K dependence (that might lead to DNA synthesis regulation), were further studied. PLD2-Y179F caused an increase in phosphorylation of p42/p44(ERK) and in the expression of G(0)/G(1) phase transition markers, p21(CIP) and PCNA, and these effects, too, were dependent on PI3K. Interestingly, Akt once activated, enabled the phosphorylation of PLD2 on residue T(175), an effect that was inhibited by LY296004. Lastly, if PLD2-Y179F is further mutated in residue K758 (PLD2 Y179F-K758R), which renders inactive a catalytic site, DNA synthesis is then abrogated, indicating that the activity of the enzyme (i.e. synthesis of PA) is necessary for the observed effects. In conclusion, the unavailability of residue Y179 on PLD2 to become phosphorylated leads to an augmentation of DNA synthesis concomitantly with MEK and AKT phosphorylation, in a process that is dependent on PI3K and independent of any extracellular stimuli. This might be critical for the maintenance of the PLD2-regulated proliferative status.